Strategi Marketing Public Relations Dealer Daihatsu Dalam Meningkatkan Penjualan Mobil Di Masa Pandemi Covid-19 - Edi Satrio Utomo; Suhendra Atmaja; Nur’aeni Nur’aeni (Universitas Majalengka, 2022)
This study aims to analyze the marketing public relations strategy used by the Daihatsu Pondok Pinang Dealer Branch to increase car sales during a pandemic, using a pull, push, and pass strategy. This study uses descriptive qualitative research methods with data collection techniques using observation, interviews and documentation. The results showed that the marketing public relations strategy of the Daihatsu Pondok Pinang Dealer Branch used push, pull, and pass to increase car sales, each having a role. However, in implementing this strategy there are several obstacles, namely cost and budget constraints in carrying out the program, the increasing number of competitors in the automotive industry business world, and structurally the public relations position does not have its own division still under a senior executive salesman who does not have full authority over decisions designed.